Daya Tarik Parfum Halal bagi Generasi Z: Mengkaji Efek Mediasi Sikap terhadap Minat Membeli - Saputra, Deky Candra; Yusril, Yusril (Al-Tijary, 2024)
As the country with the largest Muslim population in the world, Indonesia has significant potential in the utilization of halal cosmetic products. The cosmetics industry in Indonesia also shows consistent growth every year. This research focuses on perfumes, which are an integral part of the cosmetics industry. The use of perfumes is also included in the Sunnah practices performed by Prophet Muhammad SAW. This research aims to investigate the purchasing intentions of Generation Z Muslims towards halal perfumes. This expansion includes exogenous variables such as religiosity, halal logo, halal knowledge, and halal awareness, with attitude considered as a mediating variable. This research is quantitative and uses a structural equation model applying Partial Least Squares (PLS-SEM) technique. The analytical tool used in this research is Smart-PLS 3. The data collection technique was carried out using the purposive sampling method, where specific criteria were established to select respondents. The data obtained comes from primary sources and was collected through questionnaires distributed via Google Forms. The results of this research show that religiosity and halal logo do not significantly influence attitudes or intentions to purchase halal perfumes; halal knowledge and halal awareness emerge as highly important factors. Gen Z with a deeper understanding of halal principles and high awareness of halal practices show more positive attitudes and a stronger inclination to purchase halal perfumes. Furthermore, this research explains the mediating role of attitudes in the relationship between halal awareness and purchase intention, highlighting the complex pathway through which consumer perceptions and values shape purchasing decisions in the field of halal products.